Social Discourse of Fake News in French and Its Digital Social Media Literacy - Merry Andriani; Annisa Fitriani Kalsum; Gabriele Nadina Elloianza (Bina Nusantara University, 2022)
The research explored the social discourse of fake news in the French language and the French government’s efforts to overcome it with digital media literacy through social media. Fake news was getting more intense with the existence of social media as an instrument of dissemination. The fake news data were observed first, then selected according to the intensity of its distribution, and taken through social media platforms with the most users in France, namely Facebook and Twitter. Then this data set was verified and confirmed through the official fact-checking platform to ensure that the data text was fake news. This data verification method also practiced techniques socialized by the French government through a digital media literacy program. All data were analyzed qualitatively using a critical paradigm, particularly critical sociolinguistics, and post-truth theory. The analysis results show a relationship between language practice through fake news texts circulating on social media and the practice of government propaganda discourse through digital media literacy. These two practices also give rise to certain social practices and movements in French society. This also shows that digital media literacy efforts alone are ineffective enough to overcome the problems caused by fake news in society.